2009
DOI: 10.1021/es900272u
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluoroalkyl Chemicals in Pooled Blood Serum from Infants, Children, and Adults in Australia

Abstract: Polyfluoroalkyl chemicals (PFCs) have been used worldwide for more than 50 years in a wide variety of industrial and consumer products. Limited data exist on human exposure to PFCs in the Southern Hemisphere. Human blood serum collected in southeast Queensland, Australia, in 2006-2007 from 2420 donors was pooled according to age (cord blood, 0-0.5, 0.6-1, 1.1-1.5, 1.6-2, 2.1-2.5, 2.6-3, 3.1-3.5, 3.6-4, 4.1-6, 6.1-9, 9.1-12, 12.1-15, 16-30, 31-45, 46-60, and > 60 years) and gender and was analyzed for eight PFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
99
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 50 publications
11
99
4
Order By: Relevance
“…The first one was done in the years 2002-03 with pooled serum 1 9 8 0 1 9 8 1 1 9 8 2 1 9 8 3 1 9 8 5 1 9 8 6 1 9 8 8 1 9 8 9 1 9 9 0 1 9 9 1 1 9 9 3 1 9 9 4 1 9 9 5 1 9 9 6 1 9 9 7 1 9 9 9 2 0 0 0 [39] ) and estimated total global POSF production volumes, data adapted from Paul et al [1] Temporal trends of PFOS, PFOA and PFHxS in serum (whole blood concentrations multiplied by a factor of 2) of Chinese adults from Shenyang, data adapted from references that are cited following the data (values 1987: male þ female, n ¼ 15 [40] ; values 1990: male þ female, n ¼ 33 [40] ; values 1999: male, 34.5 mean age, n ¼ 36 [40] ; values 2002: male, 28.5 mean age, n ¼ 36 [40] ; values 2004: male, 21-46 mean age, n ¼ 6 [41] ; values 2008: male, 40-45 mean age, n ¼ 5 [42] ). [45] and Toms et al [46] ).…”
Section: Levels and Trends In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one was done in the years 2002-03 with pooled serum 1 9 8 0 1 9 8 1 1 9 8 2 1 9 8 3 1 9 8 5 1 9 8 6 1 9 8 8 1 9 8 9 1 9 9 0 1 9 9 1 1 9 9 3 1 9 9 4 1 9 9 5 1 9 9 6 1 9 9 7 1 9 9 9 2 0 0 0 [39] ) and estimated total global POSF production volumes, data adapted from Paul et al [1] Temporal trends of PFOS, PFOA and PFHxS in serum (whole blood concentrations multiplied by a factor of 2) of Chinese adults from Shenyang, data adapted from references that are cited following the data (values 1987: male þ female, n ¼ 15 [40] ; values 1990: male þ female, n ¼ 33 [40] ; values 1999: male, 34.5 mean age, n ¼ 36 [40] ; values 2002: male, 28.5 mean age, n ¼ 36 [40] ; values 2004: male, 21-46 mean age, n ¼ 6 [41] ; values 2008: male, 40-45 mean age, n ¼ 5 [42] ). [45] and Toms et al [46] ).…”
Section: Levels and Trends In Humansmentioning
confidence: 99%
“…[46] Samples were taken from men and women of several different age groups from urban regions. A comparison of the two Australian studies showed no temporal trend between the years 2002-03 and 2006-07 (Fig.…”
Section: Levels and Trends In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus PFASs are found almost ubiquitously in various environmental media including air (Shoeib et al, 2006;Li et al, 2011b), water (Hansen et al, 2002;Boulanger et al, 2004), sediment Benskin et al, 2011), and biota (Giesy and Kannan, 2001;Tao et al, 2006), as well as humans (Kannan et al, 2004;Toms et al, 2009). Contamination of surface water by PFASs could impact water quality of drinking water sources, thus threating human health.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PFOA and other PFCAs are used as processing aids in production of fluoropolymers like polytetrafluoroethylene (31). Despite recent restrictions on production, they remain in humans (32), generating concerns about toxicity of some PFCs, with PFOS listed recently under the Stockholm Convention (17) and some exposure guidelines proposed (33,34). This paper addresses the following: strategies and methods for monitoring contamination and exposure; current evidence of contamination of indoor environments; source identification and attribution; causes of variability in contamination of indoor environments with BFRs and PFCs and the implications for source attribution and human exposure assessment and the contribution of indoor exposure to human body burdens.…”
Section: Introductionmentioning
confidence: 99%